A Front Tracking Model for Transient Solidification of Al-7wt%Si in a Bridgman Furnace - MOONEY, ROBIN (My University, 2012)
The Bridgman furnace is widely used in industry and research. This paper outlines a working onedimensional model for tracking the columnar solidification front in a Bridgman furnace where the pulling velocity, and hence front position, change as a function of time. The front tracking model is applied to a fixed grid of control volumes using an explicit numerical finite difference scheme to solve the heat equation over a finite domain. The model is demonstrated by way of a notional scenario, namely, Bridgman furnace solidification of a 16-mm diameter rod of Al–7wt%Si. The results show how the evolution of temperature distribution, thermal history, and front position are affected by a step change in pulling velocity.
PUBLISHED
Keywords: Nanoscience & Materials; Mechanical Engineering; NUMERICAL SIMULATIONS; SOLIDIFICATION